hw07su10_soln

hw07su10_soln - Problem 7.1 Our solutions will use the...

Info iconThis preview shows pages 1–4. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Problem 7.1 Our solutions will use the fundamental z-transform pair α n u [ n ] ←→ 1 1- αz- 1 . a) X 1 ( z ) = 1 1- 1 2 z- 1 + z- 1 1- 1 3 z- 1 (sum of rational functions) = 1 + 2 3 z- 1- 1 2 z- 2 1- 5 6 z- 1 + 1 6 z- 2 (ratio of polynomials) = (1- z 1 z- 1 )(1- z 2 z- 1 ) (1- 1 2 z- 1 )(1- 1 3 z- 1 ) (product of factors) , where z 1 =- 1 / 3 + p 11 / 18 ≈ . 4484 and z 2 =- 1 / 3- p 11 / 18 ≈ - 1 . 1151. b) X 2 ( z ) = 1 2 1 1- . 9 z- 1 + 1 1 + 0 . 9 z- 1 (sum of rational functions) = 1 1- . 81 z- 2 (ratio of polynomials) = 1 (1- . 9 z- 1 )(1 + 0 . 9 z- 1 ) (product of factors) c) X 3 ( z ) = 1 2 1 1- . 9 z- 1- 1 1 + 0 . 9 z- 1 (sum of rational functions) = . 9 z- 1 1- . 81 z- 2 (ratio of polynomials) = . 9 z- 1 (1- . 9 z- 1 )(1 + 0 . 9 z- 1 ) (product of factors) d) Notice that x 4 [ n ] = (0 . 9) n u [ n ], so X 4 ( z ) = 1 1- . 9 z- 1 which is the same in all three forms. e) Notice that x 5 [ n ] = (- 1 / 2) n ( e j π 3 n / 2 + e- j π 3 n / 2) u [ n ] = 1 2- 1 2 e j π 3 n +- 1 2 e- j π 3 n 1 ECE 2025 HW #4 Solutions, Summer 2010 – July 9, 2010 and so X 5 ( z ) = 1 2 1 1 + 1 2 e jπ/ 3 z- 1 + 1 1 + 1 2 e- jπ/ 3 z- 1 ! (sum of rational functions) = 1 2 2 + cos( π/ 3) z- 1 1 + cos( π/ 3) z- 1 + 1 4 z- 2 ! = 1 2 2 + 1 2 z- 1 1 + 1 2 z- 1 + 1 4 z- 2 ! (ratio of polynomials) = 1 + 1 4 z- 1 (1 + 1 2 e jπ/ 3 z- 1 )(1 + 1 2 e- jπ/ 3 z- 1 ) (product of factors) 2 ECE 2025 HW #4 Solutions, Summer 2010 – July 9, 2010 Problem 7.2 a) We have H ( z ) = Y ( z ) X ( z ) = 1- 2 . 7 z- 3 + 1 . 8 z- 4 6- . 3 z- 1- . 5 z- 5 and so Y ( z ) = 1 20 z- 1 Y ( z ) + 1 12 z- 5 Y ( z ) + 1 6 X ( z )- 9 20 z- 3 X ( z ) + 3 10 z- 4 X ( z ) ....
View Full Document

This note was uploaded on 10/21/2010 for the course ECE 2025 taught by Professor Juang during the Summer '08 term at Georgia Tech.

Page1 / 10

hw07su10_soln - Problem 7.1 Our solutions will use the...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online